MAKING ADSORBENTS FROM ACTIVATED PALM SHELL CHARCOAL WITH THE ADDITION OF SODIUM ALGINATE POLYMER FOR CPO PURIFICATION - Krisalung Linliong Tampubolon; Rafael Remit Winardi; Zullham Effendi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Crude Palm Oil (CPO) still contains various impurities that can lower the quality of the oil, thus requiring a refining process to improve its quality. This study aimed to evaluate the effectiveness of palm shell activated carbon modified with sodium alginate as an adsorbent in CPO refining. The study employed a non-factorial Completely Randomized Design (CRD) with five levels of sodium alginate concentration (0%, 1%, 2%, 3%, and 4%) and three replications. The observed parameters included water content, impurities, free fatty acids (FFA), and the Deterioration of Bleachability Index (DOBI) value. Data were analyzed using ANOVA at a 95% confidence level. The results showed that the treatment had a significant effect (P<0.05) on all parameters. The lowest moisture content was seen in treatment N3 at 0.085%, while the lowest impurity content was in treatment N1 at 0.384%. The lowest free fatty acid value was in treatment N0 at 45.590%, and the highest DOBI value was also in treatment N0 at 0.57. The study shows that activated carbon made from palm oil shells with added sodium alginate could be a good alternative adsorbent for the CPO purification process because it can really help improve the quality of crude palm oil.